2023
DOI: 10.1002/anie.202217178
|View full text |Cite
|
Sign up to set email alerts
|

Ring Expansion Strategies for the Synthesis of Medium Sized Ring and Macrocyclic Sulfonamides

Abstract: Two new ring expansion strategies are reported for the synthesis of medium sized ring and macrocyclic sulfonamides. Both methods can be performed without using classical protecting groups, with the key ring expansion step initiated by nitro reduction and amine conjugate addition respectively. Each method can be used to make diversely functionalised cyclic sulfonamides in good to excellent yields, in a range of ring sizes. The ring size dependency of the synthetic reactions is in good agreement with the outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
(9 reference statements)
0
17
0
Order By: Relevance
“…43 Of particular interest is how to gain access to difficult medium-sized rings and macrocycles. 8,44 ■ RESULTS AND DISCUSSION Hence, we envisioned installing an -OTs functional group on an isocyanide MCR (IMCR)-based scaffold that would serve as the hub for an intramolecular aliphatic nucleophilic substitution (S N ) (Figure 2A). One of the most versatile building blocks in the MCR universe is the isocyanide moiety.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Of particular interest is how to gain access to difficult medium-sized rings and macrocycles. 8,44 ■ RESULTS AND DISCUSSION Hence, we envisioned installing an -OTs functional group on an isocyanide MCR (IMCR)-based scaffold that would serve as the hub for an intramolecular aliphatic nucleophilic substitution (S N ) (Figure 2A). One of the most versatile building blocks in the MCR universe is the isocyanide moiety.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, over the last five years, MCR chemistry has emerged as an alternative and very effective synthetic strategy for the synthesis of different sizes of artificial macrocycles. ,, Moreover, peptide multicomponent macrocyclization has been designated as a strategy able to compete with the classic peptide cyclization. , Very recently, we classified the diverse macrocyclization tactics via MCR chemistry. , Based on the pioneer work of Zhu, Yudin, Wessjohann and Rivera, we identified all the strategies, underlining the importance of introducing more synthetic approaches by which the installation of orthogonal functional groups on a primary MCR-based adduct could lead to effective macrocyclization at a secondary level . Of particular interest is how to gain access to difficult medium-sized rings and macrocycles. , …”
Section: Introductionmentioning
confidence: 99%
“…Reduction of the azide group led to the formation of a 13-membered ring. The sulfonyltriazole structure was stable during purification and storage and would be useful as a sulfonylating agent for the preparation of other compounds such as sulfonamide-macrocycles. , …”
mentioning
confidence: 99%
“…Synthetic studies started by exploring amine-based substrates of the type 5a ; our previous work showed that related ring expansions are generally faster, more exergonic and higher yielding using amine side chains compared with alcohol- 11 or thiol-based systems. 12 A Conjugate Addition/Ring Expansion (CARE) 13 cascade was devised, with phosphonamidate derivative 9 reacted with different nucleophilic primary amines (Scheme 2A). The first part of the CARE cascade reaction proceeded as expected, with amine conjugate addition taking place in each case to form amines 10a – f in good yields.…”
mentioning
confidence: 99%